Tindakan Pencegahan Kebakaran Hutan dan Lahan di Kota Samarinda - Muhammad Andre Garaldy Ramadhan; Kusnayati -; Amin Fathanah; Irfan Sofyan; Ajis Maulana; Rizki Nur Azizah; Siswanto - (Jurnal Azimut, 2019)
This study aims to determine the efforts to prevent forest and land fires in Samarinda city, East Kalimantan which will be carried out. Research is expected to provide a direct or indirect description of what efforts can be made to prevent forest and land fires, which can later be used by various stakeholders such as researchers, forestry academics and non-forestry academics. So that it can be a basis for reference in forest and land fire prevention measures in the city of Samarinda, East Kalimantan province.Primary data collection was carried out by using the interview method to BPBD Samarinda and firefighting unit (Satgasdamkar). Whereas the secondary data collection was carried out by using the document search method, in order to obtain various documents regarding forest and land fire prevention measures in Samarinda city, East Kalimantan. The interview respondents was chosen purposely and in small numbers, with the number of responses being 1 head of BPBD in Samarinda City, 1 person in the field of forest and land fire prevention in Samarinda city, and 10 surrounding communities. From the results of this study it can also be concluded that there are a number of efforts to prevent forest and land fires in Samarinda City, East Kalimantan Province which include: conducting disaster socialization, conducting disaster volunteer training, Spreading early warnings about the dangers of forest and land fires through local media ( print such as banners or bale-ho and radio) and social media such as Instagram, Facebook and others, the existence of Beje and trenches in the fuel (separating fuel and inhibiting the spread of fire) and providing water reservoirs for conducting outages, making and repairing evacuation routes, making maps of areas prone to forest and land fires.